The Medici Archive Project - Medici Archive Project (2007)
[Dt.:] Das von internationalen Stiftungen unterstützte Forschungsprojekt hat zum Ziel, das Archiv der Medici in Florenz als Volltextdatenbank online zugänglich zu machen. Bislang werden nur ausgwählte Dokumente in Transkription und englischer Übersetzung präsentiert. - [Engl.:] The mission of The Medici Archive Project is to create worldwide access to the historical data in the Medici Granducal Archive by way of a fully searchable online database. The website presents documents highlights from the Medici Granducal Archive, chosen by project staff, translated, transcribed and with historical commentary.